2016
DOI: 10.4172/2161-069x.1000446
|View full text |Cite
|
Sign up to set email alerts
|

Primary Intestinal Lymphangieactasia in a Child

Abstract: Primary intestinal lymphangiectasia is one of the causes of protein losing enteropathy in children. Three years old female child presented with anasarca, failure to thrive, anemia due to primary intestinal lymphangieactasia. Diagnosis was made by endoscopic finding with histopathology of small intestinal mucosa. She responded to diet therapy with medium chain triglycerides along with fat soluble vitamin supplementation. She is in clinical remission without loose stools, fluid retention with catch up growth on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…Hokari et al reported an inconsistently changed expression of regulatory molecules for lymphangiectasia in the duodenal mucosa of PIL patients [4]. Recently, CD55 deficiency with hyperactivation of complement, angiopathic thrombosis, and protein-losing enteropathy (the CHAPLE syndrome) has been identified as a monogenic form of PIL [5]. It can also be a component of Hennekam syndrome which is an autosomal recessive disorder characterized by the association of lymphedema, intestinal lymphangiectasia, moderate mental retardation, and facial dysmorphism [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hokari et al reported an inconsistently changed expression of regulatory molecules for lymphangiectasia in the duodenal mucosa of PIL patients [4]. Recently, CD55 deficiency with hyperactivation of complement, angiopathic thrombosis, and protein-losing enteropathy (the CHAPLE syndrome) has been identified as a monogenic form of PIL [5]. It can also be a component of Hennekam syndrome which is an autosomal recessive disorder characterized by the association of lymphedema, intestinal lymphangiectasia, moderate mental retardation, and facial dysmorphism [6].…”
Section: Discussionmentioning
confidence: 99%
“…Primary intestinal lymphangiectasia (PIL) is a rare disorder often diagnosed in children before the age of three and rarely in adolescents. This clinical condition was first identified by Waldmann as ‘idiopathic hypercatabolic hypoproteinemia’, so it is also called as Waldmann’s disease [1]. Intestinal lymphangiectasia (IL) can be primary, in which there is no predisposing condition for increased lymphatic pressures and that is probably due to congenital anatomic malformation of the lymphatics.…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 ] Since then, although several studies have investigated cases of IL, [ 5 7 ] it remains to be a rare occurrence, and cases of infants with PIL are even rarer. [ 8 , 9 ]…”
Section: Introductionmentioning
confidence: 99%